Cross-National analyses of venture capital taxation frameworks: An examination of prominent economies - Srinivas, H N; Dharanendra, M; Natesh, Manu H; Thejashree, D (The International tax journal, 2026)
This scholarly article undertakes a comparative examination of the venture capital (VC) taxation frameworks in India, the United States, Singapore, China, Japan, Australia and the United Kingdom. By concentrating on aspects such as capital gains, carried interest, fund structures, investor taxation and loss treatment, it underscores the merits and drawbacks inherent in the taxation approach of each jurisdiction. The analysis reveals that the United States, Singapore, Australia and the United Kingdom afford a more conducive and transparent landscape for VC investment, whereas India, China and Japan encounter obstacles regarding regulatory intricacies and definitional clarity. The manuscript integrates the most recent policy reforms, regulatory modifications and overarching global trends in VC taxation as of 2024–25. It culminates with pragmatic recommendations aimed at harmonising India’s VC tax framework with established international best practices.